2010
DOI: 10.1038/bmt.2010.163
|View full text |Cite
|
Sign up to set email alerts
|

High incidence of oral squamous cell carcinoma independent of HPV infection after allogeneic hematopoietic SCT in Taiwan

Abstract: Hematopoietic SCT (HSCT) is a well-recognized therapeutic procedure to prolong life and cure patients with lifethreatening hematological malignancies; however, the risk of developing secondary carcinoma may increase in longterm survivors. The objective of this study was to determine the incidence and risk factors for secondary squamous carcinoma after HSCT. Between 1984 and 2004, 170 allogeneic HSCT recipients aged 415 years, who had survived for 45 years were enrolled. Demographic data and the characteristi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
21
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 18 publications
2
21
0
Order By: Relevance
“…Oropharyngeal cancer is the most frequent form of solid cancer following HSCT, where the estimated 10‐year cumulative incidence of oral squamous cell carcinoma is 1.5% (Rizzo et al , 2009; Chen et al , 2011). The tongue is the primary cancer location (25–37% of all oral cancer cases) followed by salivary gland (15–16%) and lip (9–22%) (Kruse and Gratz, 2009; Rizzo et al , 2009).…”
Section: Lip and Oral Cancersmentioning
confidence: 99%
See 2 more Smart Citations
“…Oropharyngeal cancer is the most frequent form of solid cancer following HSCT, where the estimated 10‐year cumulative incidence of oral squamous cell carcinoma is 1.5% (Rizzo et al , 2009; Chen et al , 2011). The tongue is the primary cancer location (25–37% of all oral cancer cases) followed by salivary gland (15–16%) and lip (9–22%) (Kruse and Gratz, 2009; Rizzo et al , 2009).…”
Section: Lip and Oral Cancersmentioning
confidence: 99%
“…The tongue is the primary cancer location (25–37% of all oral cancer cases) followed by salivary gland (15–16%) and lip (9–22%) (Kruse and Gratz, 2009; Rizzo et al , 2009). Oral cancer is significantly associated with chronic graft‐versus‐host disease (GVHD) – more than 90% of oral cancer cases in HSCT recipients are preceded by GVHD, as well as with older age and male gender of patients and immunosuppressive regimens, while the role of irradiation is controversial (Demarosi et al , 2005; Kruse and Gratz, 2009; Rizzo et al , 2009; Chen et al , 2011; Mawardi et al , 2011). Solid cancers, and oral cancer in particular, are the major cause of late mortality after HSCT (Rizzo et al , 2009).…”
Section: Lip and Oral Cancersmentioning
confidence: 99%
See 1 more Smart Citation
“…One study showed that all oral SCC after HSCT demonstrated pappillomatous aspects (a sign of HPV infection) as well as chronic GVHD features (dense subepithelial lymphoid infiltrate) [16]. In other report, HPV was not associated with oral carcinogenesis after HSCT [17]. The association of HPV infection with esophageal intraepithelial neoplasia is also controversial.…”
Section: Discussionmentioning
confidence: 99%
“…The malignancy types comprise a wide spectrum of diseases associated with different risk factors [11]. For instance, squamous cell carcinomas (SCCs) of the oral cavity are more common in older patients, particularly in the presence of local cGVHD [12]. Breast cancer risk is increased for patients transplanted at a younger age and exposed to total body irradiation (TBI) [13].…”
Section: Introductionmentioning
confidence: 99%